2008
DOI: 10.1093/jn/138.1.218s
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Precision of Two Short Screeners to Assess Change in Fruit and Vegetable Consumption among Diverse Populations Participating in Health Promotion Intervention Trials

Abstract: Two short frequency questionnaires, the NCI 19-item Fruit and Vegetable Screener (FVS) and a single question on overall fruit and vegetable consumption (1-item), were evaluated for their ability to assess change in fruit and vegetable (FV) consumption over time and in response to intervention among participants in 5 health promotion trials in the Behavior Change Consortium. Cross-sectional differences and correlations of FV estimates at baseline and at follow-up were compared for the FVS (n = 315) and the 1-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 54 publications
5
44
0
1
Order By: Relevance
“…In this respect, Thompson et al (2002) showed that questionnaires with a restricted number of items and lacking a quantitative assessment of portion size do not very much affect the ability to rank subjects according to F&V intake. Furthermore, it was recently reported that a 19-item F&V screener and a single question on overall F&V had similar correlations with multiple 24-h dietary recall interviews (Peterson et al, 2008). Moreover, the correlation analysis between frequency of F&V intake and plasma vitamin concentrations observed in the present study suggests that our assessment of the frequency of F&V intake was reasonably accurate (Dauchet et al, 2004).…”
Section: Discussionsupporting
confidence: 78%
“…In this respect, Thompson et al (2002) showed that questionnaires with a restricted number of items and lacking a quantitative assessment of portion size do not very much affect the ability to rank subjects according to F&V intake. Furthermore, it was recently reported that a 19-item F&V screener and a single question on overall F&V had similar correlations with multiple 24-h dietary recall interviews (Peterson et al, 2008). Moreover, the correlation analysis between frequency of F&V intake and plasma vitamin concentrations observed in the present study suggests that our assessment of the frequency of F&V intake was reasonably accurate (Dauchet et al, 2004).…”
Section: Discussionsupporting
confidence: 78%
“…an overestimation of the extent of dietary change). 87,88 Diet records can also lead to a simplification of dietary practices, because of the high respondent burden involved in recording food intakes. 86 The multiple-day 24-hour recall also has advantages over other dietary assessment methods: it is likely to be more responsive to dietary change than either the FFQ or food habit/food pattern questionnaires; and is likely to be more accurate than shopping receipts, because they do not account for household food distribution, food wastage or food gifts/purchases without receipts, which may differ pre and post intervention.…”
Section: Blindingmentioning
confidence: 99%
“…43 62,65 A screening FFQ will probably underestimate dietary change, especially if key food sources of target nutrients cannot be reported. 89 However, a social desirability bias may also occur with a screening FFQ, 87 so the direction of bias is unpredictable.…”
Section: Blindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral measures were as follows: (a) daily fruit and vegetable intake (NCI fruit and vegetable scan [20] and Food Frequency Questionnaire [FFQ;21] in the MLP, and FFQ ¡Viva Bien! ), with the criterion set at greater than or equal to five servings a day; (b) percent of calories from saturated fat (FFQ in both studies), with the criterion set at less than 10%; (c) physical activity (frequency/week of moderate physical activity measured by the CHAMPS Activities Questionnaire for Older Adults [22] in the MLP and days/week of physical activity measured by the International Physical Activity Questionnaire [23] in ¡Viva Bien!…”
Section: Original Researchmentioning
confidence: 99%